INTELIGENCIA ARTIFICIAL Y LOS MEDIOS DE COMUNICACIÓN. DESAFÍOS DE LOS PERIODISTAS PARA CONSTRUIR LA INFORMACIÓN EN EL CANTÓN QUEVEDO AÑO 2024. - Fernandez Rodriguez, Jean Carlos (2024)
Artificial intelligence (AI) has revolutionized several industries, including journalism, improving procedures such as topic choice and news writing. However, its implementation presents ethical challenges, such as transparency in algorithms and the potential loss of journalists' independence. This study examines how Artificial Intelligence impacts decision making and information generation in the media in Quevedo canton from a moral perspective. A qualitative approach based on semi-structured interviews with local journalists was used, together with a documentary study on the application of Artificial Intelligence in journalism. The results suggest that, although journalists admit the benefits of Artificial Intelligence to speed up work, there are still concerns about algorithmic biases and misinformation. In addition, the use of these tools in Quevedo is restricted due to the absence of specific training and regulations. It is concluded that Artificial Intelligence can become a useful tool to increase journalistic effectiveness, as long as it is applied under ethical principles and human supervision. It is advisable to implement training programs in Artificial Intelligence for journalists and to define regulations that control its application in local media.